Research on chimaera with a thematic focus for life history: A scientometric analysis (Revista de Biología Marina y Oceanografía, 2022)
Chimaera, represented by 52 species, are deep-sea animals, therefore difficult to access for study; moreover, they are vulnerable to fishing due to their k-strategic characteristics. Despite being vulnerable, there are few studies on its life history, which makes it difficult to understand the population status of the species. Life-history parameters are essential in population ecology to assess the status and trends of population. In this study, it was proposed to evaluate the publication trends on Chimaera and the gaps in knowledge, analyzing which subject and species are most frequently studied. For this, the scientometric method was used, based on search of articles using a group of words directed to Chimaera in databases of bibliographic references (Scopus® and Web of ScienceTM). The articles were classified by year of publication, authors' location (at the country level), focus species and subject matter. The number of articles per year showed an exponential growth trend, indicating that studies on chimaera have been increased. Among the authors’countries, such as the United States of America and the United Kingdom, are prominent. The most studied species were: Hydrolagus colliei, Callorhinchus milii and Chimaera monstrosa. The main themes of the articles were anatomy, morphology and physiology, followed by systematics and evolution. The most diminished research topics were fishing and growth, for almost all species. Therefore, even with the growth trend, more effort and reinforcement is still required in the research of these fish, mainly in the aspects on fishery, growth, and reproduction themes.